Questionnaire for assessing the digital competence of future teachers - Maria Victoria Fernández Scagliusi; Maria Del Carmen Llorente-Cejudo (Italian Journal of Educational Technology)
This study presents the preliminary stages of a validation process for a questionnaire developed to assess the digital competencies of future teachers at the University of Bologna, focusing on students in the Pedagogy, Primary Education, and Early Childhood Education programs at the Giovanni Maria Bertin Faculty. Given the increasing importance of technology in various fields, measuring digital competencies is essential for future educators. The questionnaire, based on the “Cuestionario de Competencia Digital para Futuros Maestros” (CCDFM) by Cabero-Almenara et al. (2020), was adapted to Italian. The preliminary validation process described in this paper encompassed cultural adaptation, expert review, and a pilot test. To ensure data reliability, analytical techniques like Cronbach's alpha, KMO, and Bartlett's tests were used. Factor analysis and rotation were conducted to examine item structures, alongside factor loading tests. In a context where technology integration in education is essential, this tool promises to enhance teacher preparation and refine digital competency assessment methods. The results underscore its relevance for education professionals and researchers, confirming its potential to improve teacher training practices and broader research on digital competencies.